Effect of stress ratio and mean stress on high cycle fatigue behavior of the superalloy IN718 at elevated temperatures - Pradhan D.; Mahobia G.S.; Chattopadhyay K.; Fernando D.C.; Paulose N.; Babu S.N.N.; Singh V. (My University, 2025)
The present work shows the effect of mean stress on high cycle fatigue behavior of the superalloy IN718 at 400, 500 and 600 °C, at stress ratios (R) -1, 0.5, and 0.7. Fatigue life is decreased with increase in tensile mean stress. At high mean stress, decrease in fatigue life is associated with multiple crack initiation sites at the specimen surface. Fatigue limit is highly affected by the tensile mean stress and stress ratio, R = 0.7, since the maximum stress approaches near yield stress and causes cyclic ratcheting. © 2019 IOP Publishing Ltd.